The significance of angiogenesis in tumorigenesis and prognosis of prostate cancer - Yakovtcova, I. I.; Tkachenko, P. V.; Ivakhno, I. V. (Journal of Education, Health and Sport, 2017)
Angiogenesis is a key factor in tumor growth, invasion, and metastasis. The aim of the present study is to investigate the diagnostic and predictive value of prostatic cancer (PC) angiogenesis by immunohistochemically examination of CD34, VEGF and Ki-67 in40 cases of PC, 8 cases of nodular hyperplasia and 8 cases of intraepithelial neoplasia. It was found that the density of microvessels and intensity data of stroma but not epithelium VEGF staining in PC more than in benign pathology, and increased with risk of recurrence and as the differentiation of cancer was reduced. Results indicate that the vascularization is a sign of growth and progression of PC and may be used as predictor of the disease.